A study of the chemical and microbial changes in whole-plant corn silage during fermentation and storage: effects of packing density and sealing technique - M.E. Uriarte-Archundia; K.K. Bolsen; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 2002)
The objectives of this study with whole-plant corn silage were to determine the effects of forage density after packing, and sealing technique on yeast and mold populations; and to examine the relationship between the microbial and chemical changes in the silages during the fermentation process and storage period. Whole-plant corn was harvested at 80% milkline (36% DM) and ensiled at three densities (D): D1, 23.2; D2, 33.2, and D3, 43.3 lb/ft3. Half of the silos for each density were sealed immediately after filling (S, sealed) and the other half of the silos were sealed 48 hours after filling (DS, delayed seal). The experiment was arranged in a completely randomized design with treatments being combinations of two factors: three densities (D1, D2, D3), and two sealing techniques (S, DS). There were two 3-quart capacity PVC laboratory silos per treatment. Silos were opened after 150 days, and the chemical and microbial compositions of the silages determined. Silage pH and lactic acid content were indicative of an efficient preservation. Yeast and mold populations at day 0 were high, and most of the yeasts were lactate-assimilating yeasts (LAY). LAY populations at day 0 were high, with values of 5 log10 colony forming units (CFU) per g of fresh material. Low packing density and delayed sealing resulted in higher LAY populations (P<0.01).
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Corn silage; Aerobic deterioration; Packing density